On quasi compact spaces and some functions - Ahmad Al-Omari; Takashi Noiri (Boletim da Sociedade Paranaense de Matemática, 2018)
In this paper, we introduce and investigate a new class of sets called A -open sets which are weaker than co-zero sets. Moreover, we obtain characterizations and preserving theorems of quasi compact spaces.